Kebijakan Politik Pragmatis Strategis Maulana Hasanuddin Banten (1546-1570) terhadap Portugis - Mufti Ali (Jurnal Sejarah Citra Lekha)
This paper explores the trade relation between Banten and Portugal in the last three-quarters of the sixteenth century, with special reference to the reign period of Sultan Maulana Hasanuddin (1546-1570). The mutual relationship between these two political entities and the absence of Banten rulers in the alignment of the Muslim kings of the Archipelago against Portugal are also paid due attention. This paper used historical method, which comprises four following steps: heuristic, critic, interpretation, and historiography. The study of the European primary sources, especially letters of Portuguese Catholic missionaries, accounts of the scribes of the Portuguese viceroys in Goa India, travelogues of Portuguese merchants as well as works by the Portuguese historians, unravels a piece of very important information that the relation between Banten and Portugis can be regarded as the closest one. In addition to the pepper trade, the topic of establishing the Portuguese fortress in Banten is also dealt with by the sources. The intensive arrival of the Portuguese catholic missionaries to Banten to give spiritual guidance to their fellow citizens can be associated with the fact that many Portuguese stayed in Banten. Finally, the absence of Banten rulers in the anti-Portuguese alignment led either by Aceh (1568, 1575) or by Jepara (1551, 1574), led to conclude that the commercial policy of the Islamic kingdom of Banten is pragmatic-strategic oriented rather than ideological.